Distribution, ecological and biological features and the state of cenopopulations of species of the genus Cephalanthera Rich. (Republic of Adygea) - Sirotyuk E.; Shadge A.; Gunina G.; Khiryanov V. (Russian Journal of Earth Sciences)
There are three species of the genus Cephalanthera in the Republic of Adygea. All species are rare and listed in the Red Book of the Republic. They grow in forests of various types at altitudes from 209 m to 1724 m above sea level. The review provides a brief morphological description and some features of biology and ecology. Special attention is paid to identifying the locations of species, their phytocenotic association, analyzing the ontogenetic structure of cenopopulations and assessing their condition. Limiting factors were identified and possible ways of preserving the cenopopulation diversity of species were recommended.